ATTRIBUTES OF ORGANIZATIONAL CREATIVE CLIMATE: A PERCEPTUAL ASSESSMENT OF INDIVIDUALS (IITM JOURNAL OF BUSINESS STUDIES (JBS), 2024)
Organizations today are constantly focusing on  increasing their competitiveness. One of the  ways of increasing competitiveness is by tapping  the creative potential of the employees. One  of the best ways in which organizations’ can  capture their employees’ creativity is by creating  a climate that nurtures creativity. Having a  creative working climate nourishes and creates  a suitable working culture that enhances the  creative spark of the employees. Based on this  premise, the study attempted to determine the  attributes that facilitate the development of a  creative climate and to examine the difference  between the present state and the desired state  of organization creative climate attributes. A  sample of 78 marketing professionals were taken  from media and advertising firms and quadrant  analysis was employed for analysis. The results  highlighted the attributes that require increased  attention from organizations to enhance  employee creativity. The paper also discusses  the managerial implications and directions for  future research.
Keywords: creative climate; employee creativity; perceptual assessment